The Influence of Grammatical Hunting Method on the Interest and Learning of Class 4 Students of TMI al-Amien Prenduan on Nahwu Subject - Abdul Kirom; Moh. Fuad Salim; Izzat Amini (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
The Tarbiyatul Mu'allimien al-Islamiyah (TMI) Islamic Boarding School is an educational institution that places great importance on learning and language. One of them is learning Nahwu because it can help in speaking and writing correctly. Based on the researchers' initial observations of Regular IV class students, it was found that they tended to be passive in learning nahwu, because during the learning process many students were not focused so that the learning process was only understood by some students. so it is necessary to develop teaching methods that can involve students. To develop this method, researchers will use the Grammatical Hunt Method in Nahwu Learning, in this case the students hunt for words by circling the word horizontally, vertically, or crosswise. This research is a quantitative research with a quasi-experimental research design. The samples in this study were class IV D and IV E TMI Al-AMien Prenduan, which consisted of 54 students. Research data was obtained by giving questionnaires and tests with a number of prepared statement instruments and giving test questions. The technique of data analysis in testing the hypothesis is to use the prerequisite test and independent sample t-test. The results of this scientific research indicate that the influence of the grammar hunting method on the learning interest of fourth grade TMI Al-Amien Prenduan students in nahwu material is very effective, and this is in accordance with the independent sample t-test, we can see that the value of Sig. > 0.05, then Ha is accepted, meaning that there is a significant influence between the translation grammatical method and students' interest in learning. Likewise, based on the independent sample t-test on learning outcomes, we can see that the value of Sig. <0.05, then Ha is accepted, meaning that there is a significant effect of the translation grammar method on student learning outcomes in nahwu subject for Regular IV grade students at TMI Al-Amien Prenduan effective.